Mid-term results of complex primary total knee arthroplasty using a rotating-hinge implant - Spranz, David Maximilian; Koch, Kevin-Arno; Reiner, Tobias; Hetto, Pit; Gotterbarm, Tobias; Merle, Christian (The knee, 2022)
BACKGROUND: The indications and outcomes of semi- or fully-constrained knee implants in primary total knee arthroplasty (TKA) are still controversially discussed. The present study aims to evaluate the mid-term results and complications of a modular/non-modular rotating-hinge implant in complex primary TKA. - METHODS: Eighty-two patients (86 knees) following primary TKA were retrospectively evaluated with a mean follow-up of 63 months. The functional outcome was assessed using the American Knee Society Score (AKSS) and the Oxford Knee Score (OKS). A Visual Analog Scale (VAS) was used to determine pain levels. Implant survival and reoperation rateswere estimated using competing risk analysis. Cox regression analysis wasperformed to evaluate the influence of modularity on implant survival. - RESULTS: The survival rate with the endpoint implant revision was 90% (95 %CI:83-98%) and the survival rate with the endpoint all reoperations was 84% (95 %CI:75-94%) at 7 years. The AKSS improved significantly from 24 (SD 14.9, range:0-69) preoperatively to 83 (SD 14.3, range:57-100) postoperatively (p < 0.001); functional AKSS improved significantly from 27 (SD 24.3, range:0-100) to 46 (SD: 32.9, range 0-100) (p = 0.003), and OKS from 19 (SD: 8.3, range:5-43) to 29 (SD: 10.7, range:6-48), respectively (p < 0.0001). VAS decreased significantly from 8 (SD: 2.6, range:0-10) preoperatively to 3 (SD: 2.9, range:0-9) postoperatively (p < 0.0001). There was no significant influence of modularity on revision rates comparing modular to non-modular implants (p = 0.072). - CONCLUSIONS: The present rotating-hinge implant provides substantial improvement in function and reduction of pain with good implant survival in the mid-term. Modularity was not associated with higher rates of revision.
Available online 5 December 2021
Gesehen am 02.09.2022